Accumulation of Sulfonic Acid Groups Anchored in Covalent Organic Frameworks as an Intrinsic Proton‐Conducting Electrolyte. Issue 1 (18th October 2021) - Zhai, Lipeng; Yao, Yuze; Ma, Baiwei; Hasan, Md. Mahmudul; Han, Yuxi; Mi, Liwei; Nagao, Yuki; Li, Zhongping
Abstract: Covalent organic frameworks (COFs) are a novel class of crystalline porous polymers, which possess high porosity, excellent stability, and regular nanochannels. 2D COFs provide a 1D nanochannel to form the proton transport channels. The abovementioned features afford a powerful potential platform for designing materials as proton transportation carriers. Herein, the authors incorporate sulfonic acid groups on the pore walls as proton sources for enhancing proton transport conductivity in the 1D channel. Interestingly, the sulfonic acid COFs (S‐COFs) electrolytes being binder free exhibit excellent proton conductivity of ≈1.5 × 10 −2 S cm −1 at 25 ℃ and 95% relative humidity (RH), which rank the excellent performance in standard proton‐conducting electrolytes. The S‐COFs electrolytes keep the high proton conduction over the 24 h. The activation energy is estimated to be as low as 0.17 eV, which is much lower than most reported COFs. This research opens a new window to evolve great potential of structural design for COFs as the high proton‐conducting electrolytes. Abstract : Two new sulfonated COFs as intrinsic proton‐conducting electrolyte are constructed. The 2D COFs have rich sulfonic acid groups on the uniform 1D channel to afford the excellent proton‐conducting performance being binder free. Excellent proton conductivity of 1.5 × 10 −2 S cm −1 at 25 °C and 95% relative humidity (RH) are achieved, which is comparable with the reported proton‐conducting electrolytes.